EFFICIENCY OF PULMONARY TUBERCULOSIS CHEMOTHERAPY IN NEW CASES DEPENDING ON THE TIME OFDRUG RESISTANCE DETECTION - M. V. Burаkovа; I. A. Vаsilyevа; E. V. Vаniev; T. R. Bаgdаsаryan; A. G. Sаmoylovа (Туберкулез и болезни лёгких)
The objective of the study is to compare the efficiency of chemotherapy in new pulmonary tuberculosis patients depending on the time when multiple drug resistance was detected.Materials and subjects: 89 new patients with pulmonary tuberculosis were enrolled into the study, they all had a positive result of sputum test (at least, culture). All patients were divided into 3 groups: Group 1 (55 persons) included those with mycobacteria susceptible to rifampicin (as per the cartridge test and culture), Group 2 (16 persons) - patients resistant to rifampicin (as per the cartridge test and culture), and Group 3 (18 persons) was formed retrospectively and included patients with MDR (confirmed by culture).Results. The structure of clinical forms of tuberculosis among new cases does not depend on the drug resistance of mycobacteria. High treatment efficiency can be achieved in the new pulmonary tuberculosis cases if the initial treatment regimen was prescribed based on the results of the cartridge test with consequent correction depending on the results of the proportional method on liquid media in the automated system detecting growth of mycobacteria. If the above is provided the time of destruction healing did not depend on the drug resistance of mycobacteria, and sputum conversion was achieved in all patients of Groups 1 and 2, 71 (100 ± 1.6% ) by the 6th month of treatment.